Takhrij Hadis dalam Kitab Tafsīr Marāḥ Labīd Karya Syaikh Nawawi al-Bantani - Zaenudin Zaenudin (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2019)
Hadith which is believed to be a speech, deeds, decrees (taqrir), and all the conditions of Prophet Muhammad’s saw. second source of teachings after the Qur'an. In terms of its transmission, the hadith of the Prophet is different from that of the Qur'an. All the transmission of the verses of the Qur'an transpires as mutawatir, while the hadith of the Prophet is transmitted in part mutawatir and some others are transmitted in ahad. In interpreting the Qur'an, many scholars use the bi al-ma’sur method, or interpreting the verses of the Qur'an with other verses of the Qur'an, verses of the Qur'an with the hadith of the Prophet, and verses of the Qur'an with the agreement between the Prophet’s close friends and scholars. Even with Shaykh Nawawi al-Bantani, in his interpretations books entitled Tafsīr Marāḥ Labīd , he used the method of interpretation above. However, when interpreting the Qur'an with the hadith of the prophet, Shaykh Nawawi did not include the quality of the hadith that he meant. In addition, he is inconsistent when putting the hadith, sometimes mentioning the mukharrij and the close friends, sometimes only mentioning the close friends, and sometimes he immediately propose a hadith to the Prophet saw. As the main issue of concern in this research is how is quality of the hadith contained in the book of Tafsīr Marāḥ Labīd particularly on the second Juz of Surah al-Baqarah? As the purpose of this research is to know the quality of hadith contained in the book of Tafsīr Marāḥ Labīd particularly on the second Juz of Surah al-Baqarah. In this study, the author uses the research library. As for analyzing the data, the author uses the method of takhrij hadith and descriptive to obtain and describe the data that has been collected in full, then analyze it to get the intended results, namely to know the quality of hadith in the book of Tafsīr Marāḥ Labīb. The results of the study can be concluded that the quality of the hadiths that exist in the book of Tafsīr Marāḥ Labīb on second Juz of Surah al-Baqarah, the majority are ṣaḥiḥ. quality while the ḥasan and ḍaʻif quality hadith, there are only a few and no more than two.